Consumer perception and trust of beef food safety - Urban, Kaitlyn Nicole (Kansas State University, 2024)
American consumers’ concerns over beef food safety can affect various parts of the market and supply chain. Previous literature shows that Americans generally believe their beef is safe and that in the past, they were trustful of the regulatory government agencies (Schroeder 2007; Pennings 2001). A survey was distributed to households across the United States in 2024 asking questions regarding respondents’ familiarity with food recalls; safety perceptions of beef labels, fresh foods, and locations to eat at; factors that impact beef purchases; responsibility of ensuring safe beef; and their trust in the government and beef supply chain. This thesis analyzes perceived safety of beef labels and factors that impact a consumer purchasing beef using generalized ordered logit models. Best-worst scaling questions are used to evaluate consumer perceptions of the government and beef supply chain. To analyze results from this data, a mixed logit model is used, and shares of preferences are calculated from regression estimates. Findings in the generalized ordered logit models show that consumers perceive labels as indicative of the safety of the beef they are purchasing, and that they place higher importance on different factors that influence their purchases. Results from the mixed logit model indicate that consumers do not place much trust on the government’s ability to regulate beef food safety, and instead place their trust in grocery stores and producers to provide safe beef for consumption.
Keywords: Best-worst scaling; Beef food safety; Consumer preferences; Safety perceptions; Mixed logit; Generalized ordered logit